Web-Age Information Management 16th International Conference, WAIM 2015, Qingdao, China, June 8-10, 2015. Proceedings - Yu, Xiaohui; Dong, Xin Luna.; Li, Jian.; SUN, YIZHOU; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 16th International Conference on Web-Age Information Management, WAIM 2015, held in Qingdao, China, in June 2015. The 33 full research papers, 31 short research papers, and 6 demonstrations were carefully reviewed and selected from 164 submissions. The focus of the conference is on following topics: advanced database and web applications, big data analytics big data management, caching and replication, cloud computing, content management, crowdsourcing data and information quality, data management for mobile and pervasive computing, data management on new hardware, data mining, data provenance and workflow, data warehousing and OLAP, deep web, digital libraries, entity resolution and entity linking, and graph data management, and RDF.
Graph and Social Network -- An Influence Field Perspective on Predicting User’s Retweeting Behavior -- Realizing Impact Sourcing by Adaptive Gold Questions: A Socially Responsible Measure for Workers’ Trustworthiness -- A Coalition Formation Game Theory-Based Approach for Detecting Communities in Multi-relational Networks -- Individual Influence Maximization via Link Recommendation -- Community Detection Based on Minimum-Cut Graph Partitioning -- Coherent Topic Hierarchy: A Strategy for Topic Evolutionary Analysis on Microblog Feeds -- Age Detection for Chinese Users in Weibo -- Batch Mode Active Learning for Networked Data With Optimal Subset Selection -- Information and Knowledge -- A Question Answering System Built on Domain Knowledge Base -- Fast and Accurate Computation of Role Similarity via Vertex Centrality -- Multimodal-Based Supervised Learning for Image Search Reranking -- Novel Word Features for Keyword Extraction -- A Multi-round Global Performance Evaluation Method for Interactive Image Retrieval -- Resorting Relevance Evidences to Cumulative Citation Recommendation for Knowledge Base Acceleration -- Relevance Search on Signed Heterogeneous Information Network Based on Meta-path Factorization -- Improving the Effectiveness of Keyword Search in Databases Using Query Logs -- cluTM: Content and Link Integrated Topic Model on Heterogeneous Information Networks -- Recommender Systems -- Learning to Recommend with User Generated Content -- Combining Positive and Negative Feedbacks with Factored Similarity Matrix for Recommender Systems -- Review Comment Analysis for Predicting Ratings -- Adaptive Temporal Model for IPTV Recommendation -- RPCV: Recommend Potential Customers to Vendors in Location-Based Social Network -- Mining Dependencies Considering Time Lag in Spatio-Temporal Traffic Data -- Location Semantics Protection Based on Bayesian Inference -- Big Data -- SALA: A Skew-Avoiding and Locality-Aware Algorithm for MapReduce-Based Join -- Energy-Proportional Query Processing on Database Clusters -- SparkRDF: In-Memory Distributed RDF Management Framework for Large-Scale Social Data -- Distributed Grid-Based K Nearest Neighbour Query Processing Over Moving Objects -- An Efficient Block Sampling Strategy for Online Aggregation in the Cloud -- Computing Probability Threshold Set Similarity on Probabilistic Sets -- Region-aware Top-k Similarity Search -- A Partition-Based Bi-directional Filtering Method for String Similarity JOINs -- Fast Multiway Maximum Margin Clustering Based on Genetic Algorithm via the NystrÖm Method -- Short Papers -- DTMF: A User Adaptive Model for Hybrid Recommendation -- An Adaptive Skew Handling Join Algorithm for Large-scale Data Analysis -- NokeaRM: Employing Non-key Attributes in Record Matching -- Efficient Foreign Key Discovery Based on Nearest Neighbor Search -- OntoEvent: An Ontology-Based Event Description Language for Semantic Complex Event Processing -- Differential Trust Propagation with Community Discovery for Link-Based Web Spam Demotion -- Inferring User Preference in Good Abandonment from Eye Movements -- Private Range Queries on Outsourced Databases -- Efficient Influence Maximization Based on Three Degrees of Influence Theory -- Bichromatic Reverse kNN Query Algorithm on Road Network Distance -- IIRS: A Novel Framework of Identifying Commodity Entities on E-commerce Big Data -- Extracting Appraisal Expressions from Short Texts -- Friendship Link Recommendation Based on Content Structure Information -- Overlapping Community Detection in Directed Heterogeneous Social Network -- Efficient MapReduce-Based Method for Massive Entity Matching -- The Role of Physical Location in Our Online Social Networks -- Hierarchical Community Evolution Mining from Dynamic Networks -- Exploiting Conceptual Relations of Sentences for Multi-document Summarization -- Towards Narrative Information Systems -- Maximizing the Spread of Competitive Influence in a Social Network Oriented to Viral Marketing -- SEMR: Secure and Efficient Multi-dimensional Range Query Processing in Two-tiered Wireless Sensor Networks -- A Sampling-Based Framework for Crowdsourced Select Query with Multiple Predicates -- A Customized Schema Design Framework for Multi-tenant Database -- A Multi-attribute Probabilistic Matrix Factorization Model for Personalized Recommendation -- A Novel Knowledge Extraction Framework for Resumes Based on Text Classifier -- SimRank Based Top-k Query Aggregation for Multi-Relational Networks -- On Dynamic Top-k Influence Maximization -- Community Based Spammer Detection in Social Networks -- LDM: A DTD Schema Mapping Language Based on Logic Patterns -- Effective Sampling of Points of Interests on Maps Based on Road Networks -- Associated Index for Big Structured and Unstructured Data -- Demo Papers -- Web Knowledge Base Improved OCR Correction for Chinese Business Cards -- Shortest Path and Word Vector Based Relation Representation and Clustering -- CrowdSR: A Crowd Enabled System for Semantic Recovering of Web Tables -- A Personalized News Recommendation System Based on Tag Dependency Graph -- SmartInt: A Demonstration System for the Interaction Between Schema Mapping and Record Matching -- CDSG: A Community Detection System Based on the Game Theory.
Keywords: Information storage and retrieval; Application software; Data mining; Database management; Artificial intelligence; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management; Artificial Intelligence